Degree of pain in intravenous injection of propofol with intravenous lidocaine administration; A Literature Review Study - Agung Manik Septiana Putra; I Made Gede Widnyana (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Intravenous propofol injection is widely used for anesthesia induction and sedation, though it often causes discomfort and pain at the injection site, leading to patient anxiety. Lidocaine, a local anesthetic, has been studied for its ability to reduce this pain by inhibiting sodium channels, thereby decreasing neuronal excitability and pain transmission. Research indicates that intravenous lidocaine effectively reduces the occurrence and intensity of pain during propofol injection. This study aims to assess the effectiveness of intravenous lidocaine in minimizing pain related to propofol injection. A literature review was conducted, analyzing studies from 2018 to 2024 obtained from databases such as Google Scholar, PubMed, and ScienceDirect. Twelve articles meeting the selection criteria were reviewed. The findings consistently show that intravenous lidocaine significantly lowers the pain associated with propofol injection. Additionally, lidocaine use reduced the required propofol dosage and improved patient satisfaction. The studies suggest that administering intravenous lidocaine before or during propofol injection is a practical approach to reducing injection pain. Future research should focus on optimizing the parameters that enhance lidocaine's analgesic effects, ultimately improving patient comfort and satisfaction in procedures involving sedation.